Integrasi Pembelajaran Literasi dan Numerasi Berbasis Perpuspreneur di MI Ulul Albab Plesungan Kapas - Midya Yuli Amreta; Nadya Ayu Lifiani; Yuni Setyowati; Hanifah Anom Orchidea; Widya Mufidatul 'Ula; Mu'minatut Towafiah; Eka Duwi Ardianti; Umul Latifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the integration of literacy and numeracy learning through the Perpuspreneur program at MI Ulul Albab Plesungan Kapas, as well as to identify its supporting factors, inhibiting factors, and impact on students' competency development. This research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, librarian, and students. The findings revealed that the Perpuspreneur program integrates literacy activities through reading habits, retelling reading materials, and presenting reading outcomes, while numeracy skills are developed through simple entrepreneurial practices conducted in the library canteen. Supporting factors of the program include strong support from the school principal, adequate library facilities, active participation of teachers and students, and a school culture that promotes literacy. Meanwhile, the inhibiting factors consist of limited facilities, time constraints, differences in students’ abilities, and the low motivation of some students. The implementation of the Perpuspreneur program has positively contributed to improving students’ reading interest, numeracy skills, independence, and creativity. The study concludes that the integration of literacy and numeracy through the Perpuspreneur program can serve as an effective educational innovation in creating contextual, meaningful, and student-centered learning experiences that support the development of 21st-century competencies.